The future role of agriculture in multifunctional rural development - Kovtun, Elena; Gnatyshak, Kateryna; Chornenka, Lyudmyla (Applied Studies in Agribusiness and Commerce, 2010)
This paper is focused on analysis and evaluation of the future role of agriculture in multifunctional rural development in Ukraine and also reviewing of the significant basic factors which have influence on it.